1997
DOI: 10.1111/j.1601-0825.1997.tb00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV in oral mucosal cells

Abstract: Our results suggest that epithelial cells can be productively infected by HIV. Epithelial cells in buccal mucosa may acquire HIV in the basal layers through contact with submucosal HIV-positive lymphocytes and/or Langerhans' cells. HIV infection may also spread by inter-epithelial cell contact. As HIV infected cells mature they travel to more superficial layers and are shed into the oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 31 publications
3
39
0
1
Order By: Relevance
“…The virus was localized in the interepithelial space bound by tight junctions, suggesting epithelial cell to epithelial cell contact as a route of transmission of HIV in mucosal linings. Consistent with this hypothesis, Qureshi et al (32) reported histological studies of primary tissue samples indicating that epithelial cells were infected at the basal layer, migrated toward the superficial layers, and were then sloughed off into the oral cavity. Such results are consistent with in vitro data showing that epithelial cell lines can be productively infected with HIV-1 (9,31,43).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The virus was localized in the interepithelial space bound by tight junctions, suggesting epithelial cell to epithelial cell contact as a route of transmission of HIV in mucosal linings. Consistent with this hypothesis, Qureshi et al (32) reported histological studies of primary tissue samples indicating that epithelial cells were infected at the basal layer, migrated toward the superficial layers, and were then sloughed off into the oral cavity. Such results are consistent with in vitro data showing that epithelial cell lines can be productively infected with HIV-1 (9,31,43).…”
supporting
confidence: 53%
“…Studies of clinical specimens have identified HIV DNA and RNA in oral epithelial cells obtained from saliva (33). In mucosal tissue biopsies from HIV-infected patients, HIV-positive lymphocytes were localized in both submucosal and mucosal layers in the vicinity of epithelial cells bearing HIV-1 DNA sequences (32). By electron microscopy, HIV was detected in two-thirds of the buccal mucosal scrapings obtained from HIVseropositive patients.…”
mentioning
confidence: 98%
“…In studies in which HIV-infected cells were detected at the lymphoepithelial interface of the tonsil and adenoids, most of the virusbearing cells were colabeled for viral RNA and S100, a DC marker (29,68). In buccal biopsy samples from HIV-infected individuals, provirus was identified in lymphocytes, LC, and epithelial cells (66). As early as 3 days after application of SIV to macaque tonsillar mucosa, rare SIV-infected CD4 ϩ T cells abutting the antigen-transporting epithelium of the tonsillar crypts were identified (76).…”
Section: Vaginal Transmission (I) Tsa-ish Fiv Rna Was Detected In Cmentioning
confidence: 99%
“…Therefore, there is no evidence of appreciable changes in levels of Candida-specific Oral epithelial keratinocytes play a critical role in the pathogenesis of OPC because of their close interaction with C. albicans in the superficial epithelium. Because oral epithelial keratinocytes from HIV-infected patients contain integrated HIV proviral DNA and HIV Tat/Rev RNA (347,348), possibly acquired through contact with submucosal HIV-positive lymphocytes and/or Langerhans' cells, the anticandidal properties of these cells could be potentially impaired. However, although HIV-positive patients with OPC had a significant decrease in oral epithelial cell-mediated growth inhibition of C. albicans in vitro compared to those without OPC, there was no difference in epithelial cell activity between HIV-noninfected and -infected persons without OPC (411).…”
Section: Perturbed Mucosal Immune Defense Mechanisms Against C Albicmentioning
confidence: 99%